Fabulachia: urban, black female experiences and higher education in Appalachia. Issue 2 (4th March 2017) - Troutman, Stephanie
Abstract: This article draws on focus group conversations with black female college students attending a small, liberal arts institution in Kentucky. Based primarily on group interviews and discussions, as well as observations and analysis – a theoretical domain (referred to throughout the article as 'Fabulachia') emerged as a site-specific outcome of events and ideas regarding race, gender and identity experienced by the research participants. Specifically, 'Fabulachia' functions as a theoretical hybrid space in which urban (e.g. 'ghetto fabulous') black college student-voices find a sense of empowerment as they construct their own narratives of leaving 'the hood' to attend college in rural Appalachia. This project revises and updates previous research on race and rural identity/ies in order to situate the urban black female experience into an Appalachian context. Drawing on hip hop feminism and urban education based theoretical paradigms, the Fabulachia study seeks to give voice to black females in contemporary Appalachia, with attention to their self-proclaimed 'ghetto fabulous' identities honed in and through their urban upbringings. The unique experiences of (Fabulachian) black females are an important and largely absent part of larger conversations of the growing body of Urban education research that seeks to situate the black student/black youth and schooling experience in the US. In the Fabulachia study, a group of black female students shared personal narratives (part-oral history and part direct response) to prompts and queries about the role of hip hop culture, race and gender identity in their lives. They also discussed and debated what it means to be a black female in contemporary (often racist) Appalachia, and about how their families and urban surroundings influenced their processes of being and becoming in the context of higher educational achievement.